2020
DOI: 10.1186/s12936-020-03192-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of anti-malarial drug resistance in Democratic Republic of Congo: high variability of chloroquinoresistance and lack of amodiaquinoresistance

Abstract: Background: The loss of chloroquine (CQ) effectiveness has led to its withdrawal from national policies as a first-line treatment for uncomplicated malaria in several endemic countries, such as the Democratic Republic of Congo (DRC). The K76T mutation on the pfcrt gene has been identified as a marker of CQ resistance and the SVMNT haplotype in codons 72-76 on the same gene has been associated with resistance to amodiaquine (AQ). In the DRC, the prevalence of K76T has decreased from 100% in 2000 to 63.9% in 201… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The prevalence of CQ resistance haplotypes was assessed in parasite populations from multiple sites across Southwestern Uganda (Ibanda, Isingiro, Kiruhura, and Mbarara collected in 2010, and Kasese collected in 2015). Dominance of the mutant CVIET haplotype in the samples, and lack of the mutant SVMNT haplotype (Table 1), is consistent with what has been observed in other areas of Uganda and throughout sub-Saharan Africa during a similar time frame [5,8,20,21,26,27,40,44,54]. Additionally, the prevalence of CVIET in Group 2 samples (~ 45 %, from Kasese, Table 1) is consistent with previous findings in the region (~ 50 %, from Kanungu in 2016, [28], see Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The prevalence of CQ resistance haplotypes was assessed in parasite populations from multiple sites across Southwestern Uganda (Ibanda, Isingiro, Kiruhura, and Mbarara collected in 2010, and Kasese collected in 2015). Dominance of the mutant CVIET haplotype in the samples, and lack of the mutant SVMNT haplotype (Table 1), is consistent with what has been observed in other areas of Uganda and throughout sub-Saharan Africa during a similar time frame [5,8,20,21,26,27,40,44,54]. Additionally, the prevalence of CVIET in Group 2 samples (~ 45 %, from Kasese, Table 1) is consistent with previous findings in the region (~ 50 %, from Kanungu in 2016, [28], see Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Molecular genotyping studies have predominantly used gene-specific PCR followed by sequencing to identify resistance conferring mutations [26,27,44]. Other approaches such as ligase detection reaction-fluorescent microsphere assay [28,40,45] and the quantitative PCRbased malariaTAC [46] facilitate higher sample throughput and the parallel assessment of multiple resistance alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global prevalence of the K76T mutation known to be associated with CQ resistance was 41.5%, but this was variable from one site to another, ranging from 10.0% in Fungurume to 76.9% in Katana. In 2017, a study conducted in 10 sites (including 6 sites of the present study) reported a global prevalence of the K76T mutation of 28.5% but with a high between-regions variability ranging from 1.5% in Fungurume to 89.5% in Katana [27]. In the present study, the prevalence of K76T in patients treated with ASAQ (48.9%) was higher than in those treated with AL (37.4%) with low statistical difference (p value = 0.038).…”
Section: Discussionmentioning
confidence: 66%
“…The SVMNT haplotype associated with AQ resistance was not detected in the present study, which is encouraging for the DRC national policy for the continued use of AQ in ACT. This haplotype has not yet been reported in the DRC [19,26,27,30] whereas it was found in neighbouring countries, such as Tanzania and Angola [31,32].…”
Section: Discussionmentioning
confidence: 78%